Analisis Pengembangan Ruang Terbuka Hijau Kota Balikpapan Dengan Permodelan Spatial Multi Criteria Analysis (SMCA) - rusdiana; Hidayat, Arief; Mustofa, Umar; Pratiwi, Dwinsani (COMPACT: Spatial Development Journal, 2024)
Regional Regulation No. 12 of 2012 concerning Balikpapan City Regional Spatial Plan Year 2012-2032 and Regional Regulation No. 3 of 2019 concerning Green Open Space Management emphasize that public green space should be 30% of the total area of the city or urban area, with 20% public green space and 10% private green space. The public green space currently managed by the city government only reaches 0.57% of the total area of Balikpapan city which amounts to 50,330 ha. based on these data, the achievement of the 20% public green space target of 10,066 ha is still far from the requirements so that efforts are needed to achieve the target. Therefore, a study is needed to be able to meet the needs of RTH in terms of land analysis in determining which locations or areas have the potential as RTH in Balikpapan City, as well as how the direction of RTH development in Balikpapan City. The method used is Spatial Multi Criteria Analysis (SMCA) modeling. One of the most popular spatial multi criteria analysis techniques is AHP (Analytical Hierarchy Process), AHP analysis is based on experts in related institutions. There are 7 criteria that are influential in determining the potential of green open space in Balikpapan City, the modeling results are divided into four classes ranging from very potential, potential, less potential, to non-potential. From the potential land obtained, it is expected to fulfill the green open space needs of Balikpapan City based on the area and population. The total area of land that has the potential to be developed into green open space is 88.25 ha. With this addition, the total fulfillment of public green open space in Balikpapan City can be assumed to be 0.75%. Keywords : AHP, Potential green space land, Green Open Space, SMCA